Wheat blast management through identification of novel sources of genetic resistance and understanding of disease dynamics - Cruppe, Giovana (Kansas State University, 2020)
Wheat blast (WB), caused by the fungus Magnaporthe oryzae pathotype Triticum (MoT), emerged as a devastating disease in Brazil in 1985 and now limits wheat production in South America and South Asia. Despite 30-yrs of intensive effort, the 2N[superscript v]S translocation from Aegilops ventricosa contains the only useful, although partial and background dependent, source of WB resistance. The greatest yield losses generally occur at early stages of grain development. However, we hypothesize that leaf infection is an important player in the disease epidemiology. Our goals were to (i) identify novel sources of genetic resistance through phenotypic assays in a biosafety-level 3 laboratory in the U.S. and in the field and in growth room experiments in Bolivia and Brazil, and through genome-wide association mapping and (ii) characterize disease dynamics through characterization of MoT population diversity and determining the importance of leaf blast as a source of inoculum. Among the diverse germplasm evaluated, eight non-2N[superscript v]S genotypes showed moderate levels of WB resistance, four of which were derived from the CIMMYT breeding program and four from the wheat wild relative, Aegilops tauschii. Our results showed that newer MoT strains isolated since 2012 have higher levels of aggressiveness compared to the older T-25 isolate from 1988, decreasing the resistance of some 2N[superscript v]S-based varieties. The genome-wide association study identified 25 significant SNPs using isolate T-25, in which 21 SNPs were mapped on 2A chromosome. Highly significant linkage disequilibrium was found among these SNPs, suggesting that they may tag the same QTL. The physical position of these SNPs coincides with the 2N[superscript v]S translocation. No significant SNPs were identified with MoT isolates B-71 and 008. Removing the major effect of the 2N[superscript v]S did not reveal additional significant SNPs. QTL pyramiding analyses showed that this strategy might enhance WB resistance in certain backgrounds. The low frequency of genetic resistance coupled with the increase in aggressiveness of new isolates highlights the threat WB poses to wheat production worldwide. Two field experiments were performed in Bolivia aimed to characterize the disease progress dynamics. We followed disease development in irrigated field plots where 4-week old seedlings were inoculated with Bolivian strain 008 isolated in 2015, as well as in neighboring non-inoculated plots. The results suggested that WB spreads vertically within the plant canopy and horizontally from inoculated to non-inoculated plots. Under high levels of disease intensity, strong correlation between flag leaf and spike blast intensity was found, suggesting that leaf blast can be a reliable predictor of spike severity in a susceptible host population. Finally, whole genome sequencing analyses showed little variation in the core chromosomes between the isolate 008 and the isolates subsequently sampled from blasted spikes. These findings indicate that early-stage leaf blast can play a major role as a source of inoculum for spike infection. Surprisingly, in contrast to core chromosomes, a greater variation was found in the supernumerary mini-chromosomes from these wheat spike isolates, underscoring questions about the role of these dispensable chromosomes in virulence and aggressiveness.
Keywords: Wheat blast; Disease management; Genetic resistance; Epidemiology; Disease progress; Population diversity